2003
DOI: 10.1016/s0009-2614(03)00857-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the reactions of hydroxyl radicals with the methyl-substituted silanes SiHn(CH3)4−n (n=0 to 4) at room temperature

Abstract: The flash-photolysis resonance-fluorescence method has been employed at 293-297 K to measure rate constants for the reactions of OH with SiH 4 , Si(CH 3 )H 3 , Si(CH 3 ) 2 H 2 , Si(CH 3 ) 3 H, and Si(CH 3 ) 4 of (1.2 AE 0.2) Â 10 À11 , (3.3 AE 0.4) Â 10 À11 , (4.4 AE 0.5) Â 10 À11 , (3.1 AE 0.4) Â 10 À11 , and (1.2 AE 0.2) Â 10 À12 molecule À1 cm 3 s À1 , respectively. The uncertainties are 95% confidence intervals (see text). The results reveal that the per Si-H bond reactivity towards OH increases with the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Gas-phase kinetic studies on the reactions of organo-silicon compounds appear to have been restricted to date to studies of the reactions of OH and NO 3 radicals and O 3 with mainly methyl-substituted silanes. [21][22][23][24][25][26] Using the structure activity relationship (SAR) estimation method for OH rate coefficients with organics of Kwok and Atkinson 7 gives a rate coefficient of 3.33 Â 10 À11 cm 3 per molecule per s for the reaction of OH with TEOS, which is in excellent agreement with the value determined here experimentally. In the SAR method of Kwok and Atkinson 7 the ethoxy group in TEOS is treated as an ether group and a value of 8.4 is used as substituent factor for the "-O-" group.…”
Section: Resultssupporting
confidence: 75%
“…Gas-phase kinetic studies on the reactions of organo-silicon compounds appear to have been restricted to date to studies of the reactions of OH and NO 3 radicals and O 3 with mainly methyl-substituted silanes. [21][22][23][24][25][26] Using the structure activity relationship (SAR) estimation method for OH rate coefficients with organics of Kwok and Atkinson 7 gives a rate coefficient of 3.33 Â 10 À11 cm 3 per molecule per s for the reaction of OH with TEOS, which is in excellent agreement with the value determined here experimentally. In the SAR method of Kwok and Atkinson 7 the ethoxy group in TEOS is treated as an ether group and a value of 8.4 is used as substituent factor for the "-O-" group.…”
Section: Resultssupporting
confidence: 75%
“…In these experimental studies, 3,6 a large degree of uncertainty is noticeable in the activation energy, where values from negative to positive are possible and, therefore, must be taken with caution. Finally, Goumri et al 5 . in 2003 reported the rate constant at room temperature, (1.2 ± 0.2) × 10 –11 in cm 3 molecule –1 s –1 , in perfect agreement with the previous experimental data.…”
Section: Introductionsupporting
confidence: 79%
“…The title reaction has been scarcely studied, both experimentally 3,5,6 and theoretically, 7 where dependence of the rate constant with temperature shows contradictory results. The first experimental study was reported by Atkinson and Pitts in 1978 3 .…”
Section: Introductionmentioning
confidence: 99%
“…To our best knowledge, no theoretical attention has been paid to rate constants for H atom reactions with silicon compounds, apart from those containing Si–H. ,, Moreover, there are only a few experimental results concerning the abstraction reaction from TMS. For the H + Si(CH 3 ) 4 reaction, rate constants have been studied experimentally by Arthur et al; they were measured with the pulsed photolysis resonance absorption technique and are given by the following expression 7.5 ± 4 × 10 –11 exp[−3990 ± 300/ T ] cm 3 molecule –1 s –1 for the 425–570 K temperature range.…”
Section: Introductionmentioning
confidence: 99%